Fatores relacionados ao período pandêmico e sua possível influência na fase de aleitamento materno exclusivo nas cidades de Belém e Ananindeua – Pa/Brasil - SANTOS, Bárbara Martins de Sales (2023)
The research aimed to understand the possible factors associated with the COVID19 pandemic that may have impaired the period of exclusive breastfeeding. Cross sectional and anonymous study with 62 mothers from the cities of Belem and Ananindeua – PA/Brazil, using an online form. As a result, predominantly: 1/3 had completed higher education, 25 and 49 years old, single, monthly income of 1 to 2 minimum wages, did not participate in government aid programs, cesarean delivery, prenatal care performed at SUS, were still breastfeeding, 45% had symptoms of anxiety, depression or compulsive disorder, 63% of children fell ill in the last 6 months. 24% of women felt insecurity or fear of breastfeeding because of media news. The presence of professional prenatal guidance on pregnancy and COVID19 was absent in more than 1/3 of the women, 37% did not receive professional guidance on breastfeeding during prenatal care, and 81% did not receive guidance on breastfeeding with suspicion or diagnosis of COVID19. Of the statements heard by a family member or close person, the most frequent was: "You cannot do prenatal care or go to the hospital so as not to get COVID19". The number of times the child became ill in the last 6 months and hospitalization of the child were correlated with the period of breastfeeding with p<0,0001 and p=0,0455, respectively. This study brings a new perspective to the findings involving maternal and child nutrition and the COVID19 pandemic, and it is essential that more comprehensive policies are reformulated, for the training of health professionals in the context of coping with COVID19 and for managing news available in the media.